IL-7δ5 protein is expressed in human tissues and induces expression of the oxidized low density lipoprotein receptor 1 (OLR1) in CD14+ monocytes. (June 2017) - Rane, Lalit; Rahman, Sayma; Magalhaes, Isabelle; Ambati, Aditya; Andersson, Jan; Zumla, Alimuddin; Brighenti, Susanna; Maeurer, Markus J.
Abstract: Objectives: The 6-exon-spanning 'canonical' Interleukin-7 (IL-7c) is a non-redundant cytokine in human T-cell homeostasis that undergoes extensive alternative pre-mRNA splicing. The IL-7 gene variant lacking, exon 5 (IL-7δ5), exhibits agonistic effects as compared to IL-7c. We studied in this report for the first time the protein expression of IL-7δ5 variant in tissues and its role in monocyte activation. Methods: We visualized the expression of IL-7δ5 protein by immunohistochemistry in both healthy and malignant (human) tissues and investigated the impact of IL-7δ5 stimulation on CD14+ monocytes using gene expression analysis and flow cytometry. Results: IL-7δ5 is largely expressed by human epithelial cells, yet also by stromal cells in malignant lesions. Gene expression analysis in CD14+ monocytes, induced by the 6-exon spanning IL-7 or IL-7δ5 showed similar changes resulting in a pro-inflammatory phenotype and increased expression of genes involved in lipid metabolism. IL7δ5 was superior in inducing upregulation of the oxidised low density lipoprotein receptor (OLR), measured by flow cytometry, in CD14+ cells. Conclusion: IL-7δ5, produced from non-transformed and transformed cells, may contribute to chronic inflammatory responses and development of 'foamy' cells by increased OLR1 expression that mediates increased oxLDL uptake.